Linkage of lncRNA CRNDE sponging miR-181a-5p with aggravated inflammation underlying sepsis - Wang, Yijun; Xu, Ziqiang; Yue, Dongyou; Zeng, Zhenhua; Yuan, Weijie; Xu, Ke (Innate immunity (London, England), 2020)
This investigation was performed to verify whether lncRNA CRNDE sponging miR-181a-5p was involved with sepsis-relevant inflammatory dysfunctions. Aggregately 136 sepsis patients and 151 healthy people were recruited, and their fasting peripheral blood was gathered to detect expressions of CRNDE and miR-181a-5p. In addition, THP-1 cells were transfected with si-CRNDE, miR-181a-5p mimic, pcDNA3.1-TLR4 and si-TLR4, and then sepsis-specific inflammatory cytokines within the cells were quantified. The sponging relationships between CRNDE and miR-181a-5p, as well as between miR-181a-5p and TLR4, were ascertained by means of luciferase reporter gene assay. The experimental results revealed that over-expressed CRNDE and under-expressed miR-181a-5p were associated with shortened lifespan of sepsis patients. Mechanically, si-CRNDE-1 and miR-181a-5p mimic were able to reverse the promoting effects of LPS on production of NF-kB, TNF-α, IL-1β and IL-6 by THP-1 cells. Moreover, the expressional change of miR-181a-5p in THP-1 cells was in part owing to its being sponged by CRNDE. Lastly, TLR4, subjected to targeted modification of miR-181a-5p, was capable of disturbing the contribution of CRNDE and miR-181a-5p to THP-1 cells’ release of NF-kB, TNF-α, IL-1β and IL-6. Collectively, the CRNDE/miR-181a-5p/TLR4 axis seemed to have potential in modifying sepsis-related inflammatory pathogenesis, which offered a direction for sepsis diagnosis and treatment.